452 Do doctors themselves get screened for cervical cancer? -a questionnaire based study from western rajasthan (india). (18th September 2019) - Singh, P; Gothwal, M; Yadav, G; Sharma, P
Abstract : Objectives: To find out percentage of female doctors who have undergone screening for cervical cancer. To asses knowledge and attitude for cervical cancer screening in female doctors. To find out reasons for non-screening in those who never had any screening. Methods: This was a questionnaire based study done in female doctors of Jodhpur. After informing the purpose of study, printed questionnaire was given and asked to fill the data. Identity of the person was kept confidential Questions comprised of whether they have themselves got screened, knowledge and attitude about screening and reasons for not getting themselves screened Results: 440 forms were filled by doctors of various speciality. 50 forms were excluded as were incomplete, another 2 forms were from alternative system of medicine hence excluded. Age of participants were 23 - 62 years, with majority belonging to 25–30 years and closely followed by 30–40 years age group. 85% doctors were aware about cervical cancer screening, however only 6% of doctors had ever got themselves screened. Only 1.5% doctors had screening in last 5 years. Important reasons for non-screening were- feeling embarrassed 80%, very busy 65%more than 1 reason was cited by 20%. 19% of doctors were unmarried and majority stated screening to be done after marriage. 9% stated screening not important for them. Conclusions: This study reflects satisfactory knowledge for screening; attitude of doctors reflects those of general population. Screening for cervical cancer cannot be successful if providers are not convinced for its importance and getting screened.